1974
DOI: 10.1111/j.1939-0025.1974.tb00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Late psychosocial consequences in concentration camp survivor families.

Abstract: A study of 3 4 concentration camp survivor families treated for a six-month period in family therapy describes the effects of this traumatic experience on the second generation, and discusses the possible consequences for future generations. Results of various styles of therapeutic interventions are reported, and implications are discussed.• Two families dropped out just prior to the "six-months therapy" cut-off point. This document is copyrighted by the American Psychological Association or one of its allied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The sample did rate the early discussions of the Holocaust with family and friends as "a little." This tends to agree with Russell's (1974) finding relative to these children's inability or incapacity to discuss the Holocaust experience with their parents. Of course, it is not known whether t h s communication breakdown was fostered by the children themselves, by the parents, or by both.…”
Section: Healthsupporting
confidence: 85%
See 3 more Smart Citations
“…The sample did rate the early discussions of the Holocaust with family and friends as "a little." This tends to agree with Russell's (1974) finding relative to these children's inability or incapacity to discuss the Holocaust experience with their parents. Of course, it is not known whether t h s communication breakdown was fostered by the children themselves, by the parents, or by both.…”
Section: Healthsupporting
confidence: 85%
“…Early studies of individual cases of adolescents and families in psychoanalytical treatment showed that children of Holocaust survivors evidenced symptoms of academic failure, depression, psychosomatic problems, identity crisis, delinquency, and sexual dysfunction (Aleksandrowicz, 1970;Lipkowitz, 1973;Rakoff, 1966;Russell, 1974;Rustin & Lipsig, 1972). Trossman (1968) depicted interactional patterns based on a small number of these children studied in c h c a l treatment.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…They feared that someone would kill or steal their children. Later on, these mothers became incredibly overprotective, and warned their children constantly of hidden dangers; they regaled them with tormenting memories, endlessly reliving a past that loomed so large that they were eternally pre-occupied with it" (Russell, 1974).…”
Section: The Anorexic Patient As a "Survivor"mentioning
confidence: 99%